Development of a home-based training program for post-ward geriatric rehabilitation patients with cognitive impairment: study protocol of a randomized-controlled trail - Bongartz, Martin; Kiss, Rainer; Ullrich, Phoebe; Eckert, Tobias; Bauer, Jürgen M.; Hauer, Klaus (BMC geriatrics, 2017)
Geriatric patients with cognitive impairment (CI) show an increased risk for a negative rehabilitation outcome and reduced functional recovery following inpatient rehabilitation. Despite this obvious demand, evidence-based training programs at the transition from rehabilitation to the home environments are lacking. The aim of this study is to evaluate the efficacy of a feasible and cost-effective home-based training program to improve motor performance and to promote physical activity, specifically-tailored for post-ward geriatric patients with CI.
Gesehen am 10.04.2018